MANAJEMEN MEDIA THE CONVERSATION INDONESIA SEBAGAI MEDIA BARU - Siti Aisah Nurhalida; Dadang Rahmat Hidayat; Pandan Yudhapramesti (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
In 2017, The Conversation Indonesia media came up with unique concepts and ways of working compared to online mass media in general. This media carries the concept of science communication (Scicom) and content collaboration with academics how it works with journalists as editors. In contrast, academics or experts play the role of journalists in producing popular scientific articles as the main content. For carrying out its media, The Conversation Indonesia presents science simply and easily understood to the public with a popular article-based format based on research, podcasts, and infographic content on social media. The editing process is carried out jointly between editors who are in charge as curators and responsible for the elements of journalism in writing with academics who are controlling its substance until the writing is published. Not accepting any adverts, to maintain its sustainability, The Conversation Indonesia obtained funding from university partners and donors with writing training for academics in return.